Diretrizes para prevenção e tratamento da osteoporose induzida por glicocorticoide Guidelines for the prevention and treatment of glucocorticoid-induced osteoporosis - Rosa Maria Rodrigues Pereira; Jozélio Freire de Carvalho; Ana Patrícia Paula; Cristiano Zerbini; Diogo S. Domiciano; Helenice Gonçalves; Jaime S. Danowski; João F. Marques Neto; Laura M. C. Mendonça; Mailze C. Bezerra; Maria Teresa Terreri; Marta Imamura; et al. (Revista Brasileira de Reumatologia, 2012)
Os glicocorticoides (GC) são prescritos por praticamente todas as especialidades médicas, e cerca de 0,5% da população geral do Reino Unido utiliza esses medicamentos. Com o aumento da sobrevida dos pacientes com doenças reumatológicas, a morbidade secundária ao uso dessa medicação representa um aspecto importante que deve ser considerado no manejo de nossos pacientes. As incidências de fraturas vertebrais e não vertebrais são elevadas, variando de 30%-50% em pessoas que usam GC por mais de três meses. Assim, a osteoporose e as fraturas por fragilidade devem ser prevenidas e tratadas em todos os pacientes que iniciarão ou que já estejam em uso desses esteroides. Diversas recomendações elaboradas por várias sociedades internacionais têm sido descritas na literatura, porém não há consenso entre elas. Recentemente, o Americam College of Rheumatology publicou novas recomendações, porém elas são fundamentadas na FRAX (WHO Fracture Risk Assessment Tool) para analisar o risco de cada indivíduo e, dessa maneira, não podem ser completamente utilizadas pela população brasileira. Dessa forma, a Comissão de Osteoporose e Doenças Osteometabólicas da Sociedade Brasileira de Reumatologia, em conjunto com a Associação Médica Brasileira e a Associação Brasileira de Medicina Física e Reabilitação, implementou as diretrizes brasileiras de osteoporose induzida por glicocorticoide (OPIG), baseando-se na melhor evidência científica disponível e/ou experiência de experts. DESCRIÇÃO DO MÉTODO DE COLETA DE EVIDÊNCIA: A revisão bibliográfica de artigos científicos desta diretriz foi realizada na base de dados MEDLINE. A busca de evidência partiu de cenários clínicos reais, e utilizou as seguintes palavras-chave (MeSH terms): Osteoporosis, Osteoporosis/chemically induced*= (Glucocorticoids= Adrenal Cortex Hormones, Steroids), Glucocorticoids, Glucocorticoids/administration and dosage, Glucocorticoids/therapeutic use, Glucocorticoids/adverse effects, Prednisone/adverse effects, Dose-Response Relationship, Drug, Bone Density/drug effects, Bone Density Conservation Agents/pharmacological action, Osteoporosis/ prevention&control, Calcium, Vitamin D, Vitamin D deficiency, Calcitriol, Receptors, Calcitriol; 1-hydroxycholecalciferol, Hydroxycholecalciferols, 25-Hydroxyvitamin D3 1-alpha-hydroxylase OR Steroid Hydroxylases, Prevention and Control, Spinal fractures/prevention & control, Fractures, Spontaneous, Lumbar Vertebrae/injuries, Lifestyle, Alcohol Drinking, Smoking OR tobacco use disorder, Movement, Resistance Training, Exercise Therapy, Bone density OR Bone and Bones, Dual-Energy X-Ray Absorptiometry OR Absorptiometry Photon OR DXA, Densitometry, Radiography, (Diphosphonates Alendronate OR Risedronate Pamidronate OR propanolamines OR Ibandronate OR Zoledronic acid, Teriparatide OR PTH 1-34, Men AND premenopause, pregnancy, pregnancy outcome maternal, fetus, lactation, breast-feeding, teratogens, Children (6-12 anos), adolescence (13-18 anos). GRAU DE RECOMENDAÇÃO E FORÇA DE EVIDÊNCIA: A) Estudos experimentais e observacionais de melhor consistência; B) Estudos experimentais e observacionais de menor consistência; C) Relatos de casos (estudos não controlados); D) Opinião desprovida de avaliação crítica, com base em consensos, estudos fisiológicos ou modelos animais. OBJETIVO: Estabelecer as diretrizes para a prevenção e o tratamento da OPIG. Glucocorticoids (GC) are used in almost all medical specialties, and approximately 0.5% of the general population of the United Kingdom receives those medications. With the increased survival of patients with rheumatological diseases, morbidity secondary to the use of those medications represents an important aspect of the management of our patients. The incidences of vertebral and non-vertebral fractures are elevated, ranging from 30% to 50% of the individuals on GC for over three months. Thus, osteoporosis and frailty fractures should be prevented and treated in all patients initiating or already on GC. There are several recommendations on this topic elaborated by several international societies, but consensus still lacks. Recently, the American College of Rheumatology has published new recommendations, but they are based on the WHO Fracture Risk Assessment Tool (FRAX®) to evaluate the risk for each individual, and, thus, cannot be completely used for the Brazilian population. Thus, the Committee for Osteoporosis and Bone Metabolic Disorders of the Brazilian Society of Rheumatology, along with the Brazilian Medical Association and the Brazilian Association of Physical Medicine and Rehabilitation, has elaborated the Brazilian Guidelines for Glucocorticoid-Induced Osteoporosis (GIO), based on the better available scientific evidence and/or expert experience. METHOD OF EVIDENCE COLLECTION: The bibliographic review of scientific articles of this guideline was performed in the MEDLINE database. The search for evidence was based on real clinical scenarios, and used the following keywords (MeSH terms): Osteoporosis, Osteoporosis/ chemically induced*= (Glucocorticoids= Adrenal Cortex Hormones, Steroids), Glucocorticoids, Glucocorticoids/administration and dosage, Glucocorticoids/therapeutic use, Glucocorticoids/adverse effects, Prednisone/adverse effects, Dose-Response Relationship, Drug, Bone Density/drug effects, Bone Density Conservation Agents/pharmacological action, Osteoporosis/prevention & control, Calcium, Vitamin D, Vitamin D deficiency, Calcitriol, Receptors, Calcitriol; 1-hydroxycholecalciferol, Hydroxycholecalciferols, 25-Hydroxyvitamin D3 1-alpha-hydroxylase OR Steroid Hydroxylases, Prevention and Control, Spinal fractures/prevention & control, Fractures, Spontaneous, Lumbar Vertebrae/injuries, Lifestyle, Alcohol Drinking, Smoking OR tobacco use disorder, Movement, Resistance Training, Exercise Therapy, Bone density OR Bone and Bones, Dual-Energy X-Ray Absorptiometry OR Absorptiometry Photon OR DXA, Densitometry, Radiography, (Diphosphonates Alendronate OR Risedronate Pamidronate OR propanolamines OR Ibandronate OR Zoledronic acid, Teriparatide OR PTH 1-34, Men AND premenopause, pregnancy, pregnancy outcome maternal, fetus, lactation, breast-feeding, teratogens, Children (6-12 years), adolescence (13-18 years). GRADE OF RECOMMENDATION AND LEVEL OF EVIDENCE: A) Data derived from more consistent experimental and observational studies; B) Data derived from less consistent experimental and observational studies; C) Case reports (uncontrolled studies); D) Expert opinion without explicit critical appraisal, or based on consensus, physiological studies or animal models. OBJECTIVE: To establish guidelines for the prevention and treatment of GIO.